Research of Gear Modification of Engineering Vehicle Transmission based on Romax - Zhou Jinsong; He Fuqiang; Du Xiliang; Long Yunxiang (Jixie chuandong)
At present,there are some problems such as large vibration and short service life,and the gear tooth modification is an effective way to improve the vibration and short life of the transmission,and the cost of repair is lower than other methods. Aiming at the problems of high power hydraulic transmission,the gears of the transmission are analyzed by using Romax software. Based on the theoretical and practical experience of the gear profile research at present,the gears are optimized and found to be reasonable and the comprehensive evaluation coefficient is high. By comparing the tooth surface stress distribution and the temperature value before and after the optimization and optimization results are obtained. The results show that the gear transmission error is reduced by the gear profile modification,which makes the tooth load distribution uniform,the maximum contact temperature is reduced and the distribution is more reasonable,which enhances the smoothness of the gear transmission,increases the gear life. The research method can be used for guiding the enterprise production practice.